The spatiotemporal regulation of the Keap1–Nrf2 pathway and its importance in cellular bioenergetics. (3rd August 2015) - Dinkova-Kostova, Albena T.; Baird, Liam; Holmström, Kira M.; Meyer, Colin J.; Abramov, Andrey Y.
Abstract : The Kelch-like ECH associated protein 1 (Keap1)–NF-E2 p45-related factor 2 (Nrf2) pathway regulates networks of proteins that protect against the cumulative damage of oxidants, electrophiles and misfolded proteins. The interaction between transcription factor Nrf2 and its main negative cytoplasmic regulator Keap1 follows a cycle whereby the protein complex sequentially adopts two conformations: 'open', in which Nrf2 binds to one monomer of Keap1, followed by 'closed', in which Nrf2 interacts with both members of the Keap1 dimer. Electrophiles and oxidants (inducers) are recognized by cysteine sensors within Keap1, disrupting its ability to target Nrf2 for ubiquitination and degradation. Consequently, the protein complex accumulates in the 'closed' conformation, free Keap1 is not regenerated and newly synthesized Nrf2 is stabilized to activate target-gene transcription. The prevailing view of the Keap1–Nrf2 pathway, for which there exists a wealth of experimental evidence, is that it lies at the heart of cellular defence, playing crucial roles in adaptation and survival under conditions of stress. More recently, the significance of Nrf2 in intermediary metabolism and mitochondrial physiology has also been recognized, adding another layer of cytoprotection to the repertoire of functions of Nrf2. One way by which Nrf2 influences mitochondrial activity is through increasing the availability of substrates (NADH and FADH2 ) for respiration. Another way is through accelerating fatty acid oxidation (FAO). These findings reinforce the reciprocal relationship between oxidative phosphorylation and the cellular redox state, and highlight the key role of Nrf2 in regulating this balance.